Dietary N-carbamylglutamate supplementation improves ammonia tolerance of juvenile yellow catfish Pelteobagrus fulvidraco - Feng, Dexiang; Yang, Zhiguo; Li, Ming (Frontiers in Physiology, 2023)
Introduction: Ammonia has been of concern for its high toxicity to animals. N-carbamylglutamate (NCG) can reduce blood ammonia levels in mammals, but studies on ammonia tolerance in fish are insufficient. Methods: Juvenile yellow catfish were fed two levels of NCG (0.00% and 0.05%) for 84 days under three ammonia levels (0.00, 0.08, and 0.16 mg/L NH3). Results and Discussion: The results showed that survival rate (SUR), final body weight (FBW), weight gain (WG), and serum total protein (TP), triglycerides (TG), glucose (Glu), ornithine (Orn), citrulline (Cit) contents, and liver superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), arginase (ARG), ornithine transcarbamylase (OTC) activities decreased with the increase of ammonia levels, on the contrary, feed conversion ratio (FCR), hepatosomatic index (HSI), and serum ammonia, urea, alanine aminotransferase (ALT), aspartate aminotransferase (AST), glutamine (Gln), arginine (Arg) contents, and liver malondialdehyde (MDA), tumor necrosis factor (TNF), interleukin (IL) 1, IL 8 contents, and mRNA expressions of cu/zn sod, cat, gpx, gr, tnf ɑ, il 1, and il 8 were significantly increased. Dietary 0.05% NCG supplementation had higher SUR, FBW, WG, feed intake (FI), whole-body protein, and serum TP, total cholesterol (TC), Glu, citrulline (Cit) contents, and liver SOD, GPx, argininosuccinate synthetase (ASS), argininosuccinate lyase (ASL), inducible nitric oxide synthase (iNOS) activities compared to 0.00% NCG group, but had lower serum ammonia, urea, ALT, AST, Gln, Arg contents, and liver MDA, TNF, IL 1, IL 8 contents, and neuronal nitric oxide synthase activity. At the end of bacterial challenge, cumulative mortality (CM) increased with ammonia levels increased, but serum antibody titer (AT), lysozyme (LYZ) activity, 50% hemolytic complement, immunoglobulin (Ig) contents, respiratory burst (RB), phagocytic indices decreased with ammonia levels increased. CM in 0.05% NCG group was lower than that in 0.00% NCG group, but serum AT, LYZ activity, Ig content, RB in 0.05% NCG group were significantly higher. The correlation analysis found that iNOS was positively correlated with ASS activity. This study indicates that dietary NCG supplementation can improve the ammonia tolerance of yellow catfish, and ASS may also be the target of NCG to activate the urea cycle.